Upaya Mereduksi Budaya Pernikahan Usia Dini Di Masa Pandemic Covid-19 - Habib Husnial Pardi; Muharrar Muharrar (Research Lecturer Community-Mathematics Education Department, State Islamic University of Mataram, 2022)
This participatory action research-based service activity aims to find out the reality of early marriage which is one of the threats in destroying the younger generation. This needs serious attention from varies parties related parties, especially institutions related to this issue. To reduce the culture of early marriage through KKP-DR UIN Mataram activities, there are several programs related to efforts to reduce early marriage during the current pandemic. Data were collected by observation and interview methods with various informants, namely the community and village officials in Sesela, Tamansari, Jerigo and Montong Betok villages. The form of the program used is a socialization program. From the results of feedback and evaluation after the socialization program, it was found that public knowledge about the impact of early marriage is increasing, especially their awareness which is manifested by more intensely providing direction and advice between fellow citizens, especially to their children.